Comparative Evaluation of Antimicrobial and Smear Layer Removal Efficacy of Mangifera indica Kernel Extract as Root Canal Irrigant in Primary Molar: An In Vitro Study - S. Haripriya; Jamaluddin Mohammed Farzan; Parisa Nourouzi Baghkomeh; Sivakumar Nuvvula (International Journal of Dentistry)
Background. Endodontic therapy aims to disinfect the entire root canal system. Extracts from the kernel of Mangifera indica has the potential to be a novel root canal irrigant that has yet to be studied. Hence, the present study evaluated the antimicrobial, and smear layer removal efficacy of the M. indica kernel extract as a root canal irrigant in primary molars. Materials and Methods. Methanolic extract of M. indica was prepared using the standard method. The antimicrobial efficacy of M. indica kernel extract was determined by agar diffusion method with 3% sodium hypochlorite and distilled water as controls, and the smear layer removal efficacy was assessed under the SEM after processing the root samples with different concentrations of M. indica kernel extract with 17% EDTA and distilled water as positive and negative controls, respectively. Results. A statistically significant antimicrobial efficacy was observed with the largest mean zone of inhibition recorded with 50 μl of M. indica kernel extract at 24 hr of incubation period, when compared to sodium hypochlorite as a root canal irrigant against Enterococcus faecalis using agar diffusion method at MIC value of 0.625 mg/ml. The smear layer removal efficacy of the M. indica kernel extract was not satisfactory, when compared with EDTA as a root canal irrigant in primary molars and observed under SEM. In contrast, a complete smear layer removal was observed with 17% EDTA solution. Conclusion. M. indica kernel extract has an enhanced antimicrobial efficacy but poor smear layer removal efficacy when used as a root canal irrigant.